An introduction to world Anglicanism - Kaye, Bruce Norman, 1939- (Cambridge ; New York : Cambridge University Press, 2008)
"What is the nature of world Anglicanism in a postcolonial, global age? With talk of fragmentation constantly in the media, what does it mean to be 'Anglican'? This book presents Anglicanism as a conversation over time amongst a community of people held together by sets of practices and beliefs."--Jacket.
The nature of the story as a tradition -- Forming an Anglican nation in England -- Forming Anglican churches around the world -- Changing outlooks -- Liturgical formation -- Patterns of engagement--political -- Patterns of engagement--relating to other traditions -- Influence, organisation and power in the church -- Ministerial offices--ordination -- Ministerial offices-- ordination of women -- Ministerial offices--homosexuality and the public life of the church -- Knowledge and authority in the conversation -- Ecclesiology -- Other themes in the contemporary agenda -- Quo vadis?
Includes bibliographical references and index.
Description based on print version record.
Keywords: Anglican Communion; RELIGION -- Christianity -- Anglican; Anglikanische Kirche; Electronic books; Lehrbuch